Trends of Project Based Learning in Engineering Education from 2008 to 2023: A Systematic Literature Review Approach - Ambiyar, Ambiyar; Ema Wulansari, Rizky; Kumala Dewi, Fitrika; Fitri Ananda, Yulia; Zumroh, Zumroh (Jurnal Pendidikan Tambusai, 2024)
This research aims to find and analyze international publications on trends as well as the advantages and disadvantages of applying Project Based Learning in engineering education over the past 16 years (2008-2023). This research is limited to review and research articles only, as well as in the title and articles that have the words Project Based Learning and Engineering Education as many as 100 articles. This research uses bibliometric analysis using VOSviewer software and Microsoft Excel to analyze data taken from Science Direct. The results of the analysis show that the distribution of publications from Project Based Learning in engineering education continues to increase every year. The study results also show that the most published journal about PjBL in engineering education is Procedia - Social and Behavioral Sciences and Pengyue Guo from is the author with the highest number of citations.